2016
DOI: 10.15376/biores.11.4.9986-10001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bamboo Charcoal on Water Absorption, Contact Angle, and the Physical-Mechanical Properties of Bamboo/Low-Density Polyethylene Composites

Abstract: The use of bamboo charcoal (BC) was investigated as a filler in bambooplastic composites (BPCs) to achieve improved water resistance, physical-mechanical properties, and reduced hydrophilicity. The influence of the BC content and size on the water absorption, contact angle, density, and mechanical properties of bamboo flour/low-density polyethylene (LDPE) composites was tested. Scanning electron microscopy was used to analyse fractured and flat composite surfaces. The results indicated that the BC increased wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Frausto et al (2015) reported water absorption values of up to 16% for LMDPE composites with 15 wt% of barley particles. In another study, Chen et al (2016) reported water absorption values between 9 and 12% for composites of LDPE containing 4 to 6 wt% of bamboo particles. All these results indicated that the size of the material and their nature have a strong influence on the water absorption capacity.…”
Section: Characterization Of Nanocomposites Water Absorption Studymentioning
confidence: 97%
“…Frausto et al (2015) reported water absorption values of up to 16% for LMDPE composites with 15 wt% of barley particles. In another study, Chen et al (2016) reported water absorption values between 9 and 12% for composites of LDPE containing 4 to 6 wt% of bamboo particles. All these results indicated that the size of the material and their nature have a strong influence on the water absorption capacity.…”
Section: Characterization Of Nanocomposites Water Absorption Studymentioning
confidence: 97%
“…This phe-nomenon is quite common in the literature that studies water adsorption by materials of various types. Chen et al [49], examining the water adsorption capacity of bamboo and low-density polyethylene composites with bamboo charcoal addition in the immersion test, observed that the samples rapidly adsorbed water in the early stages of immersion. This process slowed down until the equilibrium conditions were reached.…”
Section: Trend Lines Parametersmentioning
confidence: 99%
“…The BFs was dried at 103 • C for 8 h to remove all the moisture and then treated with vinyl triethoxysilane according to the following procedure [43]. The coupling agent solution was prepared at a concentration of 4 vol% with ethanol.…”
Section: Preparation Of Bpc Samplesmentioning
confidence: 99%